Digital Financial Capability, Financial Resilience, and Sustainable Business Growth in Cambodian MSMEs: A Moderated Mediation PLS-SEM Approach - Chea Sovann (Oikonomia Review: A Journal of Applied Management, Accounting, and Business Strategy, 2026)
This study examines the structural relationships between Digital Financial Capability and Sustainable Business Growth by investigating the mediating role of Financial Resilience and the moderating effect of FinTech Adoption. A cross-sectional quantitative research design was employed, involving 364 validated responses from MSME owner-managers across the major economic regions of Cambodia. The proposed research model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) implemented in SmartPLS 4, while hypothesis testing was performed using a bootstrapping procedure with 5,000 resamples. The empirical findings indicate that Digital Financial Capability exerts a significant positive effect on both Financial Resilience (β = 0.434, p < 0.001) and Sustainable Business Growth (β = 0.245, p < 0.001). Financial Resilience also demonstrates a significant positive influence on Sustainable Business Growth (β = 0.388, p < 0.001), confirming its role as a key mediating mechanism through which digital financial capability contributes to long-term business performance. FinTech Adoption significantly moderates the relationship between Digital Financial Capability and Financial Resilience (interaction effect: β = 0.162, p = 0.002), indicating that the positive impact of digital financial capability becomes stronger as firms adopt financial technologies more extensively. These findings suggest that developing digital financial capability alone is insufficient to ensure sustainable business growth. Instead, MSMEs must complement financial competencies with the effective adoption of digital financial technologies to strengthen organizational resilience and improve long-term business sustainability. The study extends the Resource-Based View by demonstrating that digital capabilities and FinTech adoption operate as complementary strategic resources that jointly enhance organizational resilience and sustainable business growth within emerging economies.